Biosorption potential of lead tolerant fungi isolated from refuse dumpsite soil in Nigeria - Jeremiah David Bala; Faruk Kuta; Adabara Nasiru; Abdulameen Saheed Adedeji; Adel Ali Saeed Al-Gheethi; Opeyemi Habeeb Fashola (Acta Scientiarum. Biological Sciences, 2020)
Metals are non-biodegradable and recurrent in the environs. Heavy metals tolerant fungi were isolated from refuse dumpsite soil using pour plate method. These fungi were identified as Aspergillus niger, Penicillium chrysogenum and Rhizomucor sp. The fungal isolates were screened for cadmium (Cd), lead (Pb) and zinc (Zn) with concentration of 200ppm, 400ppm and 600ppm. Aspergillus niger and Penicillium chrysogenum showed high tolerance for the metals in contrast to the control. The fungi with high tolerance were used for biosorption study. However, Penicillium chrysogenum showed higher lead removal or biosorption potential of 1.07ppm, 3.35ppm and 4.19ppm as compared with Aspergillus niger with lead removal of 0.67ppm, 3.11ppm and 3.79ppm at 5th, 10th and 15th day respectively. One-way Analysis of Variance was used to interpret the data generated from the biosorption study which revealed that there was no significant different (p > 0.05) between the lead removal of Aspergillus niger and Penicillium chrysogenum on the 5th day but there was significant difference (p < 0.05) in the lead removal of Aspergillus niger and Penicillium chrysogenum on the 10th and 15th day. This study suggests the use of these fungal isolates for removal and biotreatment of heavy metal contaminated and polluted environment